ENVIRONMENTAL CERTIFICATION OF TERRITORIES OF NATURAL AND ECONOMIC SYSTEMS AND UNITED COMMUNITIES: DIGITALIZATION AND BUSINESS PROCESSES FOR CIRCULAR ECONOMY - SKRYPCHUK, Petro; SKRYPCHUK, Mykhailo; PANASIUK, Damian; RYBAK, Victor (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article reveals the issues of environmental certification of natural and economic territories systems and united communities in the context of digitalization and international business processes for circular economy. There are presented modern business models related to circular economy, such as: «Circular Suppliers»; «Resource Recovery»; «Product Life Extension»; «Sharing Platforms»; «Product as a Service». There has been outlined the strategy and means of implementation which consist in creating appropriate conditions for the development of economy in compliance with the requirements of euro integration, environmentalization, taking into account innovation and investment opportunities of Ukraine on the way to overcome the crisis in the economy, ensuring a unified policy in the field of metrological support, standardization, certification and accreditation. There have been suggested measures for the implementation of ecological certification of the territories of natural and economic systems and united territorial communities and recommendations for the introduction of innovations in the following areas: environmental management, audit, expertise, insurance, licensing, economics of nature use, metrology, standardization, certification, project management etc. There has been analyzed scientific and methodological support which should include legislative and regulatory documents of the Ministry of the Environmental Protection and Natural Resources, the Ministry of Economy of Ukraine, the EU, the WTO, ISO, the concept of TQM (Total Quality Management), the model of the European Foundation for Quality Management (EFQM), strategies and concepts concerning digitalization and environmentalization of the economy; scientific and methodological developments of the UN, FAO, etc. There have been worked out in detail business processes for environmental certification of natural and economic systems territorial communities, there have been presented methodological approaches to improving the system and scheme of certification in Ukraine and worldwide as a tool for implementing the provisions of the circular economy.